Halitosis in geriatrics: factors related to this oral problem. An observational prospective clinical study. - Fernanda Pereira de Caxias; Isabela Araguê Catanoze; Emily Vivianne Freitas da Silva; Júlia Taino Helena; Daniela Atili Brandini; Daniela Micheline dos Santos; Karina Helga Leal Turcio; Aimee Maria Guiotti (Hospital de Clínicas de Itajubá, 2020)
Objective: To identify the presence and level of halitosis in edentulous individuals with or without prostheses, before and after rehabilitation with complete dentures (CD). Methods: Patients were verbally invited to participate and signed an Informed Consent. Halitosis was analyzed by the volatile sulfur compounds measurement method in the presence and absence of the old prostheses (M1) and 15 to 30 days after the patients received their new prostheses (M2). At M1, the patients answered a questionnaire with clinical data, and the saliva type and presence/absence of tongue coating were assessed. T-test and Spearman correlation test were used, and a p-value < 0,05 was considered statistically significant. Results: Twenty-seven patients (19 women) with an average age of 67 years participated in the study. The mean time of prosthesis usage was 20.2 years. Tong coating was present in 21 patients (77,8%). A good odor level of halitosis was self-claimed in 13 (41,8%) individuals. The odor level of halitosis was significantly lower in M2 compared to M1, either with or without CD and after hygiene (p < 0,001). There was a positive and statistically significant correlation between the level of halitosis and alcoholism, smoking, prostheses hygiene method, and the presence of disease (diabetes). Conclusion: The old complete replacement of the prostheses with new ones was able to improve the odor level in a period of 15 to 30 days after the treatment. The presence of halitosis was correlated with alcoholism, smoking, denture hygiene methods, and the presence of diabetes.